Optimization Diadical Relations and Interactions in the System “Teacher-Student” - Lyurina, Tanita (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
In the article there are presented the pedagogical terms of optimization of interpersonal relations of interactive co-operation in the system “teacher – student” during individual musical lessons in the process of preparation of future teachers to a development of creative potential of students.